2014
DOI: 10.1371/journal.pone.0105203
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Science in the Wild: A Social Network Analysis of Farmer Knowledge Exchange

Abstract: Responding to demands for transformed farming practices requires new forms of knowledge. Given their scale and complexity, agricultural problems can no longer be solved by linear transfers in which technology developed by specialists passes to farmers by way of extension intermediaries. Recent research on alternative approaches has focused on the innovation systems formed by interactions between heterogeneous actors. Rather than linear transfer, systems theory highlights network facilitation as a specialized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 25 publications
7
120
0
5
Order By: Relevance
“…As an example, interview partners reported that farmers usually closely observe the practices of each other and "tease" each other, for example when one is late with a particular task or when fields are getting "untidy." This fits quite well with an observation made by Wood et al (2014), that farmers' information sources are mainly other farmers, and before they try something new they want to know if fellow farmers are partaking and what their experiences are. Sutherland et al (2012) also found that social relations among farmers plays a crucial role in adopting new farming methods and it has also been shown for the uptake of agri-environmental measures (see Lastra-Bravo et al 2015 for examples).…”
Section: Network Of Information Flows Regulation and Social Pressusupporting
confidence: 87%
“…As an example, interview partners reported that farmers usually closely observe the practices of each other and "tease" each other, for example when one is late with a particular task or when fields are getting "untidy." This fits quite well with an observation made by Wood et al (2014), that farmers' information sources are mainly other farmers, and before they try something new they want to know if fellow farmers are partaking and what their experiences are. Sutherland et al (2012) also found that social relations among farmers plays a crucial role in adopting new farming methods and it has also been shown for the uptake of agri-environmental measures (see Lastra-Bravo et al 2015 for examples).…”
Section: Network Of Information Flows Regulation and Social Pressusupporting
confidence: 87%
“…The characteristics of these networks were quite different, likely reflecting the particular social-ecological characteristics of the community and supporting the need for context-specific approaches to agricultural extension and innovation (Hellin 2012;Wood et al 2014). For example, the farmer knowledge network in Black Bay (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Narayanam and Narahari (2011) indicate that the relationships actors establish in a network play an important role in the diffusion of ideas and information. While extensionists are important they are often not the firstly ranked information source which are generally other farmers and input dealers (Sligo et al, 2005;Solano et al, 2003;Wood et al, 2014;Thuo et al, 2014). Different studies have found different effects of links with extension agents on adoption of new or improved technologies and practices.…”
Section: The Role Of Extension In a Broader Information Network Suppomentioning
confidence: 99%